(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article explores the interconnected roles of classroom management and a teacher’s approach in fostering an effective learning environment. It highlights strategies for maintaining order, addressing behavioral challenges, and building positive relationships with students. The discussion emphasizes the importance of adaptability, cultural competence, and professional development in meeting diverse student needs. Additionally, the article underscores the value of creating a structured, inclusive, and engaging classroom atmosphere while leveraging technology to enhance learning experiences. By integrating these elements, educators can inspire student participation, promote respect, and ensure academic and emotional growth in a dynamic educational landscape.